Text Analysis in Teaching Translation - Gabriel Angel Quiroz Herrera; Carlos Arturo Muñoz Torres (HOW, 2016)
The idea that translators begin to translate once they get a hold of the source language (SL) text is widely spread and controverted. As a cognitive and metacognitive strategy, text analysis is vital in translation training in order to gain a good expertise in translation. A two-phase model is discussed in this paper: an overall text evaluation first and then a deep analysis are undertaken. In the former, students learn to apply and identify background knowledge, document sources, text length, price, and difficulty among other factors. In the latter, students analyse titles, text layout, communication situation, text types, genre, etc. The strategies and methodology to attain these phases in the translation process are explained step-by-step. Additionally, student samples will be shown as further illustrations.